2004
DOI: 10.1161/01.cir.0000146380.08401.99
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Effects of Resistance Training on Central Arterial Compliance

Abstract: Background-Reductions in the compliance of central arteries exert a number of adverse effects on cardiovascular function and disease risk. Endurance training is efficacious in increasing arterial compliance in healthy adults. We determined the effects of resistance training on carotid arterial compliance using the intervention study design. Methods and Results-Twenty-eight healthy men 20 to 38 years old were randomly assigned to the intervention group (nϭ14) and the control group (nϭ14). Control subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
211
3
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(237 citation statements)
references
References 43 publications
11
211
3
12
Order By: Relevance
“…As baseline levels of BP are subjected to hold-down force, the pressure signal obtained by tonometry was calibrated by equating the carotid MAP and diastolic blood pressure to the brachial artery value. 12,14 The coefficient of variation for inter-observer reproducibility of AI was 5% in our laboratory. Hypertension was defined as systolic blood pressure (SBP) X140 or diastolic blood pressure X90.…”
Section: Subjectsmentioning
confidence: 79%
See 1 more Smart Citation
“…As baseline levels of BP are subjected to hold-down force, the pressure signal obtained by tonometry was calibrated by equating the carotid MAP and diastolic blood pressure to the brachial artery value. 12,14 The coefficient of variation for inter-observer reproducibility of AI was 5% in our laboratory. Hypertension was defined as systolic blood pressure (SBP) X140 or diastolic blood pressure X90.…”
Section: Subjectsmentioning
confidence: 79%
“…The participants had various physical activity levels, and none were regularly engaged in weight training. 14 None of the participants smoked and they were not taking steroids or hormone replacement therapy. None of the young women were taking oral contraceptives.…”
Section: Subjectsmentioning
confidence: 99%
“…Similar findings have been seen with increases in stiffness in the central arteries following resistance training in both acute and training studies. 12,41 Miyachi et al 11 reported a 19% decrease in central arterial compliance following 4 months of strength training in 14 young men compared to sedentary controls, but with no changes in peripheral compliance. It should be noted that not all studies have shown an increase in central arterial stiffness following resistance training, 42 but these studies included different populations and employed a different exercise prescription.…”
Section: Aementioning
confidence: 99%
“…Confounding the recommendation employing RE as an exercise regimen, recent evidence indicates that RE may cause increased arterial stiffness in young, healthy normotensive individuals. 11,12 However, these findings are controversial, as not all studies show an increase in arterial stiffness with resistance training. 13,14 Increases in arterial stiffness, which are associated with increased mortality and morbidity, can lead to decreases in blood flow because of increased peripheral resistance.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to exercise, there is evidence that chronic dynamic training has a beneficial effect on AS, 7 whereas chronic resistance exercise may have an unfavourable influence on central haemodynamics. 8,9 Nevertheless, there is little and inconsistent data about the effects of acute bouts of exercise on AS. Acute aerobic exercise was found to induce either an increase 10 or a decrease 11,12 in central AS, whereas studies on acute bouts of resistance exercise showed either an increase 13 or no effect 14 on central AS.…”
Section: Introductionmentioning
confidence: 99%